The mediating effect of Work Engagement on the relation between Career Adaptability and OCB - Hadla, Fatima (2020)
Employees are the asset of every organization. They are the resource that grant the organization a competitive advantage in the market place. Due to fast changes taking place in today’s market, organizations are relying more on employees with higher work engagement level, adaptability and the willingness to go the extra mile. This study explores the relationship between career adaptability and organization citizenship behavior (OCB). It also proposes the mediation of work engagement between career adaptability and OCB. One hundred and forty employees working in the private sector in Lebanon participated in our survey that was then analyzed using SPSS and PROCESS software. Results indicated that career adaptability has significant positive influence on OCB and work engagement, work engagement in turn is positively associated with OCB and acted as a partial mediator for career adaptability and OCB. Furthermore, future recommendations and practical implications of the study are discussed along with limitations.